Analisis Efisiensi Penggunaan Modal Kerja Keuangan Syariah - Ekaningsih, Lely Ana Ferawati; Rohmah , Faizzahtur (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
The purpose of this study is to analyze the efficiency of the use of Islamic financial working capital at BMT UGT Sidogiri, Glenmore Branch, Banyuwangi Regency. This study uses applied research. Sampling using a purposive sampling technique. The data source used is secondary data in the form of financial reports of Islamic entities for the 2015-2019 period. The use of working capital is calculated using the liquidity ratio, debt ratio, and working capital profitability ratio. The results of the study indicate that the liquidity ratio in the form of a current ratio experienced fluctuations that tended to decrease while the debt ratio in the form of a debt-to-equity ratio experienced good fluctuations while the ratio of total debt to total assets experienced fluctuations that changed then the profitability ratio increased at the beginning of the year and decreased at the end of the year. The conclusion shows that the efficient working capital used at BMT UGT Sidogiri Glenmore Branch, Banyuwangi Regency has proven to be very efficient, this shows that BMT UGT Sidogiri Glenmore Branch, Banyuwangi can be trusted in managing its working capital as QS. Al-Anfal verse 27:8.